Sexual Health Care, Sexual Behaviors and Functioning, and Female Genital Cutting: Perspectives From Somali Women Living in the United States. Issue 3 (23rd March 2016) - Connor, Jennifer Jo; Hunt, Shanda; Finsaas, Megan; Ciesinski, Amanda; Ahmed, Amira; Robinson, Beatrice "Bean" E.
Abstract : We investigated the sexual values, attitudes, and behaviors of 30 Somali female refugees living in a large metropolitan area of Minnesota by collecting exploratory sexual health information based on the components of the sexual health model—components posited to be essential aspects of healthy human sexuality. A Somali-born bilingual interviewer conducted the semistructured interviews in English or Somali; 22 participants chose to be interviewed in Somali. Interviews were translated, transcribed, and analyzed using descriptive statistics and thematic analyses. Our study findings highlighted a sexually conservative culture that values sexual intimacy, female and male sexual pleasure, and privacy in marriage; vaginal sexual intercourse as the only sanctioned sexual behavior; and the importance of Islamic religion in guiding sexual practices. Findings related to human immunodeficiency virus (HIV) revealed HIV testing at immigration, mixed attitudes toward condom use, and moderate knowledge about HIV transmission modes. Female genital cutting (FGC) was a pervasive factor affecting sexual functioning in Somali women, with attitudes about the controversial practice in transition. We recommend that health professionals take the initiative to discuss sexual health care and safer sex, sexual behaviors/functioning, and likely challenges to sexual health with Somali women—as they may be unlikely to broach these subjects without permission and considerable encouragement.